Relationship Between Taste Sensitivity Of Phenylthio Carbamide And Obesity Among Male And Female Population Of Udaipur, Rajasthan (India) (Applied Biological Research, 2022)
The present study was aimed to assess the prevalence of phenylthiol carbamide (PTC) taste sensitivity, and its relation with obesity among the  male and female population of Udaipur, Rajasthan (India). The study was  carried out on 235 individuals (94 males and 141 females) aged ≥ 40 years.  The food preferences were recorded through personal interview method,  and standard anthropometric procedures were followed to measure anthro pometric variables. Body mass index (BMI) and waist to hip ratio (WHR)  were also calculated. The subjects were asked to taste PTC solution and  classified as tasters and non-tasters. The overall tasters among the studied  population were 169 (71.9%). Distribution of PTC taste sensitivity were  more frequent among female (taster = 60.35%, non-taster = 59.09%) than  male (taster = 39.6%, non-taster = 40.9%). The PTC taster's both male and  female, showed higher BMI as compared to the non-taster individuals.  Considering the life style variables, the smoking status showed a significant  difference between tasters and non-tasters (χ2 = 3.97; p = 0.047), but no  difference was observed for alcohol consumption (χ2 = 0.77; p = 0.381). The  present study provides background information about PTC taste  sensitivity's phenotypic frequency distribution which may serve as useful  interactions of taste sensitivity with other associated lifestyle variables.
Keywords: Alcohol consumption; BMI; smoking; taste sensitivity; waist to hip ratio